WEAVING BADUY IDENTITY IN MEDIA SIGN OF WEAVING BADUY IDENTITY IN MEDIA “DESA KANEKES” WEBSITE (SPATIAL SEMIOTIC DISCOURSE ANALYSIS) - Santy Yulianti, M.Hum.; Tommy Chirstomy, Ph.D. (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2021)
This paper explores the contribution of media in changing the image of an indigenous community by controlling some information of the tribal values possessed by the Baduy tribe in the media. The media that represented Baduy Tribe to the public is called